Avaliação do potencial uso do estômago do peixe xaréu Caranx hippos (Linnaeus, 1766) como fonte de proteases ácidas para aplicações industriais e biotecnológicas - Silva, José Alécio Ferreira da (2020)
Over the past few decades there has been a growing at fish consumption, mainly due to the population growth as well as higher demand for healthy food. This growth brings challenges about the management of waste generated in the processing of this fish. Solid residues such as scales, fins and viscera are generally discarded in natura causing an environmental damage. One of the most captured fish species in Brazilian Northeastern coast is the Caranx hippos, popularly known as crevale jack. In this way, this work aimed to evaluate the potential use of the C. hippos stomach as a source of aspartic proteases for industrial and biotechnological applications. For this, a homogenate was obtained from the stomach. The homogenate was submitted to an acidification and "salting-out" process, and a protein fraction (F60) was collected. Using F60, tests were performed for specific acid proteolytic activity, physical-chemical characterization, zymogram and chemical agents effects. From the stomach it was possible to obtain an enzymatic fraction with a purification rate of 1.6 folds and a 49.4% of yield. The F60 specific proteolytic activity observed was 1,404.6 ± 3.09 U/mg. The optimum temperature for proteolytic activity was 50 ºC and the thermal stability was observed between 25 ºC and 50 ºC. For F60 proteolytic activity were observed an optimal pH and pH stability rages between pH 1.5 to 3.5 and pH 1.5 to 7.0, respectively. Were observed a total inhibition of enzymatic activity in the presence of pepstatin A, and a low inhibition in the presence of heavy metals. Through the zymogram it was possible to observe the presence of two proteolytic bands. F60 maintained more than 50% of its proteolytic activity in the presence of NaCl 15%. Through the obtained data it is possible to reach that the stomach of the fish C. hippos is a promising alternative source of aspartic proteases with interesting characteristics for industrial and biotechnological applications.